3m+12=-m-(m+13)

Simple and best practice solution for 3m+12=-m-(m+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+12=-m-(m+13) equation:


Simplifying
3m + 12 = -1m + -1(m + 13)

Reorder the terms:
12 + 3m = -1m + -1(m + 13)

Reorder the terms:
12 + 3m = -1m + -1(13 + m)
12 + 3m = -1m + (13 * -1 + m * -1)
12 + 3m = -1m + (-13 + -1m)

Reorder the terms:
12 + 3m = -13 + -1m + -1m

Combine like terms: -1m + -1m = -2m
12 + 3m = -13 + -2m

Solving
12 + 3m = -13 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
12 + 3m + 2m = -13 + -2m + 2m

Combine like terms: 3m + 2m = 5m
12 + 5m = -13 + -2m + 2m

Combine like terms: -2m + 2m = 0
12 + 5m = -13 + 0
12 + 5m = -13

Add '-12' to each side of the equation.
12 + -12 + 5m = -13 + -12

Combine like terms: 12 + -12 = 0
0 + 5m = -13 + -12
5m = -13 + -12

Combine like terms: -13 + -12 = -25
5m = -25

Divide each side by '5'.
m = -5

Simplifying
m = -5

See similar equations:

| M-18/2=4 | | m-41= | | 8.75/2/5= | | .5(y+8)=4(y-6) | | (2x+50)+(x+10)=180 | | 2(d+4)=8 | | -2x+2=3(4+x) | | 4(3n-1)=2n+2(5n-2) | | 8x-10=2x+4 | | 2y-2=.14 | | y=(.5x-3) | | 5(b+9)+7= | | -7=-3c | | x/41+89=93 | | 10x+4x+2+9=4x+3+9x | | b^2+7b+2=-10 | | 0.2x+5=2 | | (2y+7)(3y-7)=0 | | x+3x+6x-8=180 | | 5/6x1/2 | | a-x+c=d | | 9x/5-3/2=6 | | 1500+.05x=1865 | | 56=14+7x | | 9n^3/3t^7r^3 | | (29b-3)-7(4b+3)=-4 | | 4x=2y-yx | | -(3x-6y-9)= | | 2/3k-9=5 | | -4=1x-12 | | 6u^2-22uv+20v^2=0 | | 5p-(-10)=-5 |

Equations solver categories